Understanding the plasticity of amorphous alloys via the interpretation of structural evolution inside a shear band - Lee, C.-M.; Park, K.-W.; Lee, B.-J.; Shim, J.-H.; Lee, J.-C. (2009)
The effect of the initial packing structure on the plasticity of amorphous alloys was investigated by tracing the structural evolution of the amorphous solid inside a shear band. According to the molecular dynamics simulations, the structural evolution of the amorphous solids inside the shear band was more abrupt in the alloy with a higher initial packing density. Such a difference in the structural evolution within the shear band observed from the amorphous alloys with different initial packing density is believed to cause different degrees of shear localization, providing an answer to the fundamental question of why amorphous alloys show different plasticity. We clarify the structural origin of the plasticity of bulk amorphous alloys by exploring the microstructural aspects in view of the structural disordering, disorder-induced softening, and shear localization using molecular dynamics simulations based on the recently developed MEAM (modified embedded atom method) potential.
Keywords: Amorphous solids; Bulk amorphous alloys; Microstructural aspects; Modified embedded atom methods; Molecular dynamics simulations; Packing density; Packing structure; Shear localizations; Structural disorder; Structural disordering; Structural evolution; Structural origin; Dynamics; Molecular dynamics; Plasticity; Shear bands; Amorphous alloys